Samariscus neocaledonia, a new righteye flounder (Teleostei: Pleuronectiformes: Samaridae) from New Caledonia - Kawai, Toshio; Amaoka, Kunio; Séret, Bernard (Zootaxa, 2011)
A new righteye flounder, Samariscus neocaledonia sp. nov., is described on the basis of two specimens collected in deep waters (244–278 m) around New Caledonia. The new species is easily distinguished from its 18 congeners in having a combination of 78–81 dorsal fin rays, 62–65 anal fin rays, five pectoral fin rays, ca. 55–62 lateral line scales, and 10 abdominal and 31–32 caudal vertebrae.